A case report and literature review of barium sulphate aspiration during upper gastrointestinal examination. Issue 47 (November 2017) - Yan, Gao-Wu; Deng, Jiang-Fa; Bhetuwal, Anup; Yang, Guo-Qing; Fu, Quan-Shui; Chen, Hong; Hu, Na; Zeng, Hao; Fan, Xiao-Ping; Yan, Gao-Wen; Wu, Xiao-Lin
Abstract: Rationale: Even though barium sulphate aspiration during upper gastrointestinal examination is a well-known phenomenon, complication such as long-term lung injury and death may still occur. This may depend upon the concentration, amount, anatomy, or certain predisposing factors. Patient concerns: A 47-year-old woman who had a barium swallow to screen for foreign body in esophagus. Diagnoses: Chest radiographs demonstrated massive barium sulphate depositions in her trachea and inferior lobe of right lung. Interventions: A chest x-ray was done that revealed massive barium sulphate depositions in her trachea and lower lobe of right lung. As the patient did not have further complaints, she requested a transfer to West China Hospital of Sichuan University, the hospital being near her residence, for further treatment. She eventually recovered and was discharged after 1 week. Outcomes: There were 23 articles (22 English and 1 Chinese with 17 men and 11 women) included in the study. The risk factors of barium sulphate aspiration are dysphagia (10/28, 35.71%) followed by esophageal obstruction caused by tumor (5/28, 17.86%) and foreign body in esophagus (3/28, 10.71%). Infants (5/28, 17.86%) are also one of the high-risk population. Both the lungs were affected in most of the patients (21/28, 75%). Majority of the presentation in patients (21/28, 75%) were dyspnea, hypoxemia, acute respiratory distress syndrome (ARDS), or respiratory failure. Few patients (7/28, 25%) showed no symptoms or mild symptoms such as cough and fever. Barium sulphate aspiration can be life-threatening with a high risk of death (nearly 40%). Lessons: When performing an upper gastrointestinal examination with barium sulphate, careful consideration of concentration and amount of barium sulphate and that of risk factors should be undertaken so as to avoid life-threatening aspiration.